Further mechanical considerations between Polar and SRM mobile ergometer systems during laboratory-based high-intensity, intermittent cycling activity - Gordon, R. S.; Franklin, K. L.; Davies, B.; Baker, J. S. (Research in Sports Medicine, 2007)
The purpose of this article is to outline mechanical issues related to the use of the Polar S710 heart monitor with Power Unit when compared with the SRM Powercrank system. There are issues outlined in this article that refer to the suitability of the Polar S710 for the quantification of performance during downhill cycling that relate to chain vibration, chain tension, and time interval sampling rates.